2019
DOI: 10.1111/modl.12547
|View full text |Cite
|
Sign up to set email alerts
|

Material Moments: Teacher and Student Use of Materials in Multilingual Writing Classroom Interactions

Abstract: This qualitative study examines moments in the multilingual classroom when materials become prominent in whole‐class interactions. Despite the critical impact that materials can have on classroom discourse and learning/teaching, research on actual usage of materials in second language (L2) classroom interactions has been scarce compared with the effort devoted to the development and assessment of L2 materials (Guerrettaz & Johnston, 2013). This study examines students’ and instructors’ use of materials in a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 63 publications
1
42
0
Order By: Relevance
“…It is only recently that researchers have begun exploring how materials are used inside language classrooms (Matsumoto, 2019). After extensively reviewing empirical studies of materials use in language classrooms, Tomlinson and Masuhara (2018) identified two primary research foci, namely teachers' approaches or techniques of adaptation (how) and the rationales for their adaptation (why).…”
Section: Materials Use Research In Eltmentioning
confidence: 99%
See 1 more Smart Citation
“…It is only recently that researchers have begun exploring how materials are used inside language classrooms (Matsumoto, 2019). After extensively reviewing empirical studies of materials use in language classrooms, Tomlinson and Masuhara (2018) identified two primary research foci, namely teachers' approaches or techniques of adaptation (how) and the rationales for their adaptation (why).…”
Section: Materials Use Research In Eltmentioning
confidence: 99%
“…To address this issue, this heuristic study has developed an analytical tool to represent and examine the ways in which teachers use materials in language classrooms, i.e., the materials use arc (MUA) model. It builds on the assumption that classroom teaching encompasses a range of adaptive activities where teachers selectively leverage materials to design and enact instruction in the classroom ecology (Guerrettaz & Johnston, 2013;Matsumoto, 2019). MUA refers to a pedagogical episode with a distinct pedagogical purpose entailing a series of interactions among teachers, learners, and materials (Li, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the abundant and insightful literature on materials development and evaluation has concentrated on the production, content, and intent of materials themselves, research in materials use focuses on relationships between participants and the materials. A fundamental aim of materials use is to better understand what occurs when participants actually use lesson materials (Matsumoto, 2019). Guerrettaz et al (2018) define materials use as "ways that participants in language learning environments actually employ and interact with materials" (p. 38).…”
mentioning
confidence: 99%
“…Because materials use is such a new area of research, studies remain scarce. Existing studies have addressed diverse topics such as materials use in whole-group, teacherfronted interaction (Guerrettaz & Johnston, 2013;Thoms, 2014), teacher adaptation of materials (Shawer, 2010;Marcos Miguel, 2015), the physical handling of documents by students (Jakonen, 2015), use of video-based materials by participants (Grandon, 2018), and materials use in writing classes (Matsumoto, 2019). In addition, Garton and Graves (2014) edited one of the first book-length treatments on materials use.…”
mentioning
confidence: 99%
See 1 more Smart Citation